Relationship between physical fitness factors and the ability to maintain joint lower limb torques during the latter half of the 400 meter running event - Ogata, M.; Manabe, Y.; Takamoro, M. (Journal of Human Movement Studies, 2005)
The purpose of this study was to characterise differences in sprint ability and lower limb joint torque between sprints of maximal efforts vs. those performed under fatigued conditions. We also examined the relationship between differences in sprint ability and joint torque with lower limb muscular endurance and aerobic and anaerobic work capacities. Sprint motions of eleven male Sprinters were analysed during a 45-55m section of an 80m running event and during a 355-365m section of a 400m running event. Muscular endurance of the lower limbs, maximal oxygen intake, and oxygen deficit were also measured. Running speed, stride length, stride frequency, knee extension torque, hip flexion torque, and hip extension torque were significantly higher in the maximal sprint than in the fatigued sprint. The ability to maintain stride frequency significantly correlated with sprint speed maintenance and the ability to maintain hip joint flexion and extension torques. The ability to maintain hip joint flexion torque significantly correlated with maximal oxygen intake, while the ability to maintain hip joint extension torque significantly correlated with muscular endurance of the knee and hip äs well äs with maximal oxygen intake. These results suggest that the ability to maintain joint torque during the fatigued sprint is an important determinant of performance during a 400m running event and that muscular endurance of the lower limbs influences the maintenance of joint torque.